Upaya Meningkatkan Sikap Tanggung Jawab dan Hasil Belajar Keterampilan Bermain Sepakbola Melalui Model Pembelajaran Kooperatif Tipe STAD di SMP Darussalam Cimanggu - Rama Cipta Prasetia; Ruman Ruman; Latif Turhasan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
The aim of this research was to determine the effect of the student team achievement division type cooperative learning model on the attitude of responsibility and learning outcomes of football playing skills at SMP Darussalam Cimanggu. The sample used was 20 students who took part in football extracurriculars. This research uses an experimental method with a pre test post test control group design. The results of the paired sample t test show that the significance value (2-tailed) for the attitude of responsibility in the experimental group is 0.013<0.05, while playing skills are 0.000<0.05, therefore H0 is rejected and Ha is accepted. The results of the independent sample t test stated that the significance value (2-tailed) for the attitude of responsibility was 0.024<0.025, while the playing skills were 0.000<0.025, so it can be concluded that, on average, the attitude of responsibility and the results of learning football playing skills in the group experiment is different from the control group. Apart from that, from the results of the N-Gain Score test, it was found that the average percentage of student responsibility attitudes for the experimental group was 44.68%, the value was in the range of 40-45, which means that the use of the student team achievement division type cooperative learning model was less effective. Meanwhile, the average percentage of playing skills in the experimental group was 65.57%, the value was in the range of 56-75, which means that the use of the student team achievement division type cooperative learning model was quite effective.